Evolutionary reconstruction supports the presence of a Pleistocene Arctic refugium for a large mammal species. (18th September 2017) - Klütsch, Cornelya F. C.; Manseau, Micheline; Anderson, Morgan; Sinkins, Peter; Wilson, Paul J.
Abstract: Aim: The presence of refugia in the Canadian High Arctic has been subject to debate for decades. We investigated the potential existence of Arctic refugia during the Pleistocene for a large mammal species in the Canadian Archipelago because if these refugia were present, reconsideration of the evolutionary histories of North American fauna and flora beyond the major refugia of Beringia and south of the Laurentide and Cordilleran Ice Sheets would be required. Peary caribou ( Rangifer tarandus pearyi ), identified as a subspecies based on morphological characteristics, inhabits the Canadian Arctic Islands and Boothia Peninsula. Previous studies demonstrated incomplete lineage sorting of mitochondrial DNA interpreted as a Beringian origin but were based on small sample sizes. Location: Canadian Arctic. Major taxa studied: Mammals: caribou ( Rangifer tarandus ). Methods: We used two molecular markers (microsatellites and mitochondrial DNA) and approximate Bayesian computations (ABC) testing the hypotheses of colonization out of Beringia into the Arctic Islands following the Last Glacial Maximum (LGM) or a divergence from Beringia significantly before the end of the LGM within a different refugium. Results: The coalescent‐based analyses rejected a recent Beringian origin with subsequent colonization, instead supporting a divergence of Peary caribou from Beringia ~100, 000 years ago linking it to the last interglacial/early Wisconsin Glacial Stage (125, 000–75, 000 years ago). Admixture on Banks Island with Beringian‐derived barren‐ground caribou is indicative of post‐Pleistocene secondary contact; further supporting a divergent history of Peary caribou within a separated Arctic refugium. Main conclusions: Our results offer support for the existence of an Arctic refugium for large mammal species and add to the increasing evidence of such refugia in North America. This has significant implications on understanding the evolution and conservation of Arctic species, particularly in light of sensitivities and adaptive potential to a rapidly changing climate.